Expanding the phenotypic spectrum of non-alcoholic fatty liver disease and hypertriglyceridemia - Meroni, Marica; Longo, Miriam; Paolini, Erika; Tria, Giada; Ripolone, Michela; Napoli, Laura; Moggio, Maurizio; Fracanzani, Anna Ludovica; Dongiovanni, Paola (Frontiers in Nutrition, 2022)
Background and aims Hypertriglyceridemia is a common feature of metabolic syndrome (MetS), as well as of non-alcoholic fatty liver disease (NAFLD), which is considered the hepatic manifestation of MetS. Fat accumulation in hepatocytes may alter mitochondrial homeostasis predisposing to advanced liver disease. Here, we report a case of a 40-year-old woman with early aggressive NAFLD due to severe hypertriglyceridemia that ensued from a combination of genetic variants and additional metabolic risk factors. Methods Genetic screening was performed by using whole-exome sequencing (WES), and mitochondrial structures were evaluated by TEM. Results At presentation, the patient is reported to have hepatomegaly, hypertriglyceridemia, and raised transaminases. Genetic analysis revealed that the patient beard heritable alterations in genes implicated in lipid handling, among which APOB, APOE, CETP, and HSPG2, accompanied by missense mutations in genes involved in mitochondrial function, i.e., AK2, ALG6, ASPA, NDUFAF1, POLG, and TMEM70. Abdominal ultrasound (US) and transient elastography were suggestive of severe hepatic steatosis and fibrosis. A liver biopsy confirmed the diagnosis of non-alcoholic steatohepatitis (NASH)-related fibrosis. Thus, to better outline whether mutations involved in lipid remodeling and mitochondrial function may also affect organelles’ morphology, we exploited TEM. Along with multifaceted abnormalities of mitochondrial architecture that have been already observed in patients with NAFLD, astonishing ultrastructural defects, such as mitochondrial vacuolization, sub-compartmentalization, and onion-like mitochondria, were identified. Conclusion The anomalies reported may expand the phenotypic spectrum of mitochondrial abnormalities observed in patients with NAFLD, which may contribute to the switching toward a progressive disease.